Regulator of G protein signaling-1 facilitates ovarian cancer development by modulating NF-kB signal pathway - Liu Shengnan; Xi Jiayan; Sun Meng; Li Li; Cai Shengyun; Xu Mingjuan (Scientific Reports)
Abstract Regulator of G protein signaling 1 (RGS1) is known to be highly expressed in various tumors, but its specific effects and regulatory mechanism in ovarian cancer (OC) progression are not well understood. To delve into the tumor biology, a predictive risk model for OC was developed, incorporating RGS1, PRKG2, CD24, and ABCB1, with RGS1 exhibiting the strongest correlation. The model’s reliability and validity were confirmed through Kaplan-Meier analysis, receiver operating characteristic (ROC) curve, and principal component analysis (PCA). The risk score was validated as an independent indicator of overall survival, and a nomogram model was created to predict overall survival. Moreover, RGS1 expression was found to be up-regulated and associated with a poor prognosis in OC. Functional studies revealed that deleting RGS1 inhibited OC cell proliferation both in vitro and in vivo, while overexpression of RGS1 enhanced cell proliferation. Additionally, blocking the NF-kB pathway was shown to impede RGS1-induced proliferation, and overexpression of p65 partially reversed the effects of RGS1 deletion, promoting the tumorigenic properties of OC cells. These findings suggest that RGS1 could be a valuable biomarker for predicting prognosis and a potential novel therapeutic target for OC treatment.